Distributed Computing and Artificial Intelligence, Special Sessions, 15th International Conference - Rodríguez, Sara; Prieto, Javier; Faria, Pedro; Kłos, Sławomir; Fernández, Alberto; Mazuelas, Santiago; Jiménez-López, M. Dolores; Moreno, María N.; Navarro, Elena M. (Advances in Intelligent Systems and Computing,, 2019)
This book presents the outcomes of the 15th International Conference on Distributed Computing and Artificial Intelligence, held in Toledo (Spain) from 20th to 22nd June 2018 and hosted by the UCLM, and which brought together researchers and developers from industry, education and the academic world to report on the latest scientific research, technical advances and methodologies. Highlighting multi-disciplinary and transversal aspects, the book focuses on the conferences Special Sessions, including Advances in Demand Response and Renewable Energy Sources in Smart Grids (ADRESS); AI- Driven Methods for Multimodal Networks and Processes Modeling (AIMPM); Social Modelling of Ambient Intelligence in Large Facilities (SMAILF); Communications, Electronics and Signal Processing (CESP); Complexity in Natural and Formal Languages (CNFL); and Web and Social Media Mining (WASMM). .